Breast pain in a patient on dialysis: a rare manifestation of calcific uraemic arteriolopathy. (9th January 2015) - Buscher, Konrad; Gabriëls, Gert; Barth, Peter; Pavenstädt, Hermann
Abstract : A 63-year-old woman presented with progredient bilateral breast pain. Her medical history included rheumatoid arthritis, AA amyloidosis and end-stage renal disease treated by peritoneal dialysis. Inflamed skin alterations of the breast and laboratory values suggested mastitis non-puerpuralis but antibiotics did not resolve the symptoms. Sonography and mammography showed severe vessel calcification suggesting calcific uraemic arteriolopathy (calciphylaxis) as a rare complication of chronic kidney disease. Treatment included intensified haemodialysis, thiosulfate application, analgaesia and wound management leading to significant improvement, however, without complete remission.